Β‐Adrenoceptor regulates contraction and inflammatory cytokine expression of human bladder smooth muscle cells via autophagy under pathological hydrostatic pressure. Issue 8 (19th September 2020) - Chen, Guo; Jin, Xi; Luo, Deyi; Ai, Jianzhong; Xiao, Kaiwen; Lai, Junyu; He, Qin; Li, Hong; Wang, Kunjie
Abstract: Aims: Abnormal intravesical pressure created by partial bladder outlet obstruction (PBOO) triggered the progression from chronic inflammation to fibrosis, initiating structural and functional alterations of bladder. To elucidate the underlying mechanisms of contraction and inflammatory response, we investigated the isolated human bladder smooth muscle cells (hBSMC) under pathological hydrostatic pressure (HP) mimicking the in vivo PBOO condition. Methods: hBSMCs were subjected to HP of 200 cm H2 O to explore the contraction and inflammatory cytokine expression of hBSMC treated with β‐adrenoceptors (ADRBs) and/or autophagy signaling pathway agonists and/or antagonists. Results: We showed that pathological HP induced the release of the proinflammatory cytokines, including monocyte chemotactic protein‐1, regulated upon activation normal T cell expressed and secreted factor, and interleukin‐6. HP downregulated ADRB2 and ADRB3 expression, which was consistent with the results of the PBOO rat model. ADRB2 or autophagy activation repressed pathological HP‐induced proinflammatory cytokine production. ADRB2, ADRB3 or autophagy activation ameliorated the HP‐enhanced contraction. The increased contraction and autophagy activity by ADRB2 agonist under HP conditions were reversed by pretreatment with antagonists of adenosine monophosphate‐activated protein kinase (AMPK). Conclusion: The present study provides evidence that the ADRB3 agonist suppresses hBSMC contraction under pathological HP conditions. Moreover, the ADRB2 agonist negatively regulates the contraction and inflammatory response of hBSMCs through AMPK/mTOR‐mediated autophagy under pathological HP. These findings provide a theoretical basis for potential therapeutic strategies for patients with PBOO.